Profile of Fatty Acids, Amino Acids, Carotenoid Total, and α-Tocopherol from Flying Fish Eggs - Aulia Azka; Nurjanah Nurjanah; Agoes Mardiono Jacoeb (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Flying fish are found in waters of eastern Indonesia, which until now is still limited informationabout nutritional content. The purpose of this research was determine the composition offatty acids, amino acids, total carotenoids, α-tocopherol flying fish eggs (Hyrundicthys sp.).The composition of fatty acid was measured by gas chromatography (GC), while amino acids,total carotenoids, α-tocopherol was measured by High performanced Liquid Chromatography(HPLC). Egg contained 22 fatty acids such as saturated fatty acid 29.71%, monounsaturated fattyacid 7.86%, and polysaturated fatty acid 13.64%. The result showed that eggs flying fish contained17 amino acids, such as essential amino acid 14.96% and non-essential amino acids 20.27%. Eggscontained a total carotenoid of 245.37 ppm. α-tocopherol content of flying fish eggs by 1.06 ppm.Keywords: Amino acids, carotenoid total, fatty acid, flying fish egg, α-tocopherol